Kontribusi Istri Nelayan dalam Meningkatkan Perekonomian Keluarga di Kelurahan Tembeling Tanjung Kecamatan Teluk Bintan - Rahmadeni, Yozi (Jurnal Masyarakat Maritim, 2019)
This study the authors used descriptive research type. Sampling technique is done by purposive sampling. Primary data obtained by observation (Observation) and using an interview guide. Techniques of data analysis using qualitative methods and frequency tables. Population and samples in this study were the wives of fishermen who work in the Village Tanjung Tembeling. This study aims to determine the role of the fisherman's wife in improving the economy of the family. The usefulness of this study is expected to be the results of this study in particular input Bintan regency governments in developing existing potential for the region's development and research are also expected to be a reference and comparison to other studies related to this research. The results generally show that the wives of fishermen who work to help her family make ends meet motivated by economic factors and to supplement her family's income. Most educational level fisherman's wife owned only a primary school, where the wives of fishermen working in the informal sector, which does not require high education and skills